A method for preparing a solid electrolyte interface of an electrolyte material
By performing plasma fluorination treatment on the electrolyte surface of the lithium-ion battery and building a LiF interface layer, the problem of lithium dendrites in lithium-ion batteries is solved, and the chemical stability and current density of the battery are improved.
Patent Information
- Application Number
- CN202411931661.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
There are interface problems in the application of existing solid electrolytes in lithium-ion batteries, resulting in uneven distribution of lithium ions and the generation of lithium dendrites, affecting the safety and performance of the battery.
By performing plasma surface fluorination treatment on the electrolyte surface, a fluorinated layer is introduced, and during the coating of the molten negative electrode, a lithium metal reacts with the fluorinated element in the fluorinated layer to form a lithium fluorinated compound, a LiF interface layer is constructed, and the interface contact between the electrolyte and the negative electrode is improved.
It effectively reduces the interface resistance, promotes uniform deposition of lithium ions, inhibits the formation of lithium dendrites, and improves the chemical stability and current density of the electrolyte.
Smart Images

Figure CN119764585A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials, and in particular relates to a method for preparing a solid electrolyte interface of an electrolyte material. Background Art
[0002] In lithium-ion batteries using liquid electrolytes, lithium dendrites are easily formed on the surface of the lithium metal anode, which usually pierce the diaphragm and cause the battery to burn. The system using high-capacity lithium metal anodes not only has higher energy density, but also uses non-flammable solid electrolytes, which can fundamentally solve the safety problem of liquid battery combustion. Solid electrolytes are one of the ideal candidate materials to match lithium metal, with excellent ionic conductivity performance.
[0003] At present, the main reason limiting the application of solid electrolytes in batteries is the interface problem. The interface problem on the negative electrode side is mainly related to the surface lithium affinity and repellency of the electrolyte. The surface energy of molten lithium metal is high, and it forms a spherical shape under the action of surface tension, causing the electrolyte to show lithium repellency and produce high interface resistance. This situation will cause lithium ions Li + During the intercalation and deintercalation, the surface of lithium metal is unevenly distributed, thus inducing the formation of lithium dendrites.
[0004] Research work to prevent the growth of lithium dendrites has mainly focused on modifying the interface between modified LLZO (lithium-containing garnet electrolyte) and metallic lithium. Among the interface improvement methods used, one method is to use the alloying reaction between lithium and another metal (such as zinc Zn, antimony Sb, strontium Sr) to inhibit the growth of lithium dendrites; another method is to introduce an intermediate buffer layer to improve the interface contact between LLZO and metallic lithium, thereby preventing the growth of lithium dendrites. However, these interface improvement methods are greatly limited by the complex preparation process and high production cost. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a solid electrolyte interface of an electrolyte material, which effectively reduces the cost and complexity of the interface improvement method, while solving the problem that the negative electrode side of the existing electrolyte is severely lithium-phobic and unstable.
[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0007] The present invention provides a method for preparing a solid electrolyte interface of an electrolyte material, comprising the following steps:
[0008] S1. Placing the electrolyte in a reaction chamber of a plasma device and introducing a fluorine-containing gas for vacuum fluorination treatment to obtain an electrolyte having a fluorinated layer on one surface;
[0009] S2. A solid electrolyte interface layer is in situ constructed between the electrolyte and the negative electrode through the reaction between the fluoride layer on the surface of one side of the electrolyte and the negative electrode, wherein the component of the solid electrolyte interface layer is LiF.
[0010] Furthermore, the S1 comprises the following steps:
[0011] S11, obtaining the electrolyte prepared by sintering;
[0012] S12, polishing the prepared electrolyte after sintering and placing it in the plasma equipment reaction chamber, and extracting the air in the plasma equipment reaction chamber by a mechanical pump and a molecular pump in turn, so that the internal pressure of the plasma equipment reaction chamber is lower than a preset pressure threshold;
[0013] S13, introducing fluorine-containing gas into the reaction chamber of the plasma equipment at a preset flow rate until the pressure is stable, turning on the power of the plasma equipment, and performing fluorination treatment based on the set RF power and sputtering time to obtain an electrolyte with a fluoride layer on one surface.
[0014] Furthermore, the electrolyte is one of a garnet-type electrolyte, a perovskite-type electrolyte, a NASICON-type electrolyte or a sulfide electrolyte.
[0015] Furthermore, the fluorine-containing gas includes one or any combination of fluorine gas F2, carbon fluoride CF4, nitrogen trifluoride NF3, sulfur hexafluoride SF6, hydrogen fluoride HF, and trifluoromethane CHF3.
[0016] Furthermore, the S2 comprises the following steps:
[0017] S21, dissolving the negative electrode at 200° C. to 300° C. and coating the negative electrode on the fluoride layer on one surface of the electrolyte;
[0018] S22, adding the electrolyte dropwise to the other side surface of the electrolyte;
[0019] S23, covering the positive electrode on the other side of the electrolyte after the electrolyte solution is added, and encapsulating it, so that the fluoride layer on the surface of one side of the electrolyte reacts with the negative electrode, and completing the in-situ construction of a solid electrolyte interface layer between the electrolyte and the negative electrode.
[0020] Furthermore, the negative electrode is one of a metal lithium sheet, a lithium aluminum alloy, a lithium indium alloy, a lithium magnesium alloy, and a lithium titanium alloy; the electrolyte is one of LB002, LB372, LB001, and LB224; the positive electrode is one of lithium iron phosphate LiFePO4, lithium cobalt oxide LiCoO2, lithium manganese oxide LiMnO4, lithium nickel cobalt manganese oxide NCM, and lithium nickel cobalt aluminum oxide NCA.
[0021] The beneficial effects of the present invention are as follows: a solid electrolyte interface preparation method for an electrolyte material provided by the present invention introduces a fluoride layer on the surface of the electrolyte by plasma surface fluorination treatment, and in the process of molten negative electrode coating, the metal lithium reacts with the fluorine element in the fluoride layer to form a lithium fluoride compound, which can effectively break the surface tension of liquid metal lithium, so that the electrolyte can have good wettability and lithium affinity, which is conducive to the uniform spreading of lithium metal on the electrolyte surface, thereby reducing the interface resistance; after the present invention performs fluorination treatment on the electrolyte surface, a fluoride film is generated on the surface of one side of the electrolyte, and the metal lithium negative electrode reacts with the fluoride film to generate LiF, that is, a new interface layer is introduced on the original basis, and the new interface layer has extremely high mechanical strength and chemical stability, can effectively inhibit the side reaction at the interface, and promote the lithium ion Li + The uniform deposition of lithium ions is achieved and the formation of lithium dendrites is suppressed, thereby improving the current density and chemical stability that the electrolyte can withstand.
[0022] Other advantages of the present invention will be analyzed in more detail in subsequent embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 This is a flow chart of the steps of a method for preparing a solid electrolyte interface of an electrolyte material in embodiment 1 of the present invention.
[0025] Figure 2 Schematic diagram of the structure of the modified electrolyte material in Example 1 of the present invention.
[0026] Figure 3 Schematic diagram of impedance comparison of electrolyte materials in Example 7 of the present invention.
[0027] Figure 4 This is the charge and discharge cycle curve of the modified electrolyte material at 0.1C in Example 7 of the present invention.
[0028] Figure 5 This is the charge and discharge cycle curve of the unmodified electrolyte material at 0.1C in Example 7 of the present invention.
[0029] Among them: 1. positive electrode; 2. electrolyte material; 3. solid electrolyte interface; 4. negative electrode. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention generally described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] like Figure 1 As shown, in one embodiment of the present invention, a method for preparing a solid electrolyte interface of an electrolyte material is provided, comprising the following steps:
[0033] S1. Placing the electrolyte in a reaction chamber of a plasma device and introducing a fluorine-containing gas for vacuum fluorination treatment to obtain an electrolyte having a fluorinated layer on one surface;
[0034] The S1 comprises the following steps:
[0035] S11, obtaining the electrolyte prepared by sintering;
[0036] The electrolyte is one of a garnet-type electrolyte, a perovskite-type electrolyte, a NASICON-type electrolyte or a sulfide electrolyte.
[0037] In this scheme, the garnet-type electrolyte is Li7La3Zr2O 12 ; The perovskite electrolyte is Li 3x La 23- x Ti3O3; the NASICON-type electrolyte is LATP and LAGP; the NASICON-type electrolyte is a sodium superionic conductor, a non-flammable solid electrolyte material with high ionic conductivity and excellent chemical and electrochemical stability.
[0038] S12, polishing the prepared electrolyte after sintering and placing it in the plasma equipment reaction chamber, and extracting the air in the plasma equipment reaction chamber by a mechanical pump and a molecular pump in turn, so that the internal pressure of the plasma equipment reaction chamber is lower than a preset pressure threshold;
[0039] S13, introducing the fluorine-containing gas into the reaction chamber of the plasma equipment according to the preset flow rate until the pressure is stable, turning on the power of the plasma equipment, and performing fluorination treatment based on the set RF power and sputtering time to obtain an electrolyte with a fluoride layer on one surface. In this embodiment, the preset flow rate is 50sccm to 100sccm, the RF power is 300W to 600W, and the sputtering time is 5min to 20min.
[0040] The fluorine-containing gas includes one or any combination of fluorine gas F2, carbon fluoride CF4, nitrogen trifluoride NF3, sulfur hexafluoride SF6, hydrogen fluoride HF, and trifluoromethane CHF3.
[0041] S2, through the reaction between the fluoride layer on the surface of one side of the electrolyte and the negative electrode, a solid electrolyte interface layer is in situ constructed between the electrolyte and the negative electrode, wherein the component of the solid electrolyte interface layer is LiF. In this scheme, the main component of the solid electrolyte interface layer is LiF, which has extremely high mechanical strength and chemical stability, and can promote the lithium ion Li + It can ensure uniform deposition of lithium ions and effectively inhibit the side reactions and formation of lithium dendrites at the interface, thereby improving the cycle stability.
[0042] The S2 comprises the following steps:
[0043] S21, dissolving the negative electrode at 200° C. to 300° C. and coating the negative electrode on the fluoride layer on one surface of the electrolyte;
[0044] The negative electrode is one of a metal lithium sheet, a lithium aluminum alloy, a lithium indium alloy, a lithium magnesium alloy, and a lithium titanium alloy; the electrolyte is one of LB002, LB372, LB001, and LB224;
[0045] S22, dripping the electrolyte onto the other side of the electrolyte; in this scheme, the amount of electrolyte dripped is 2-10uL / cm 2 .
[0046] S23, covering the positive electrode on the other side of the electrolyte after the electrolyte solution is added, and encapsulating, so that the fluoride layer on the surface of one side of the electrolyte reacts with the negative electrode, and completing the in-situ construction of a solid electrolyte interface layer between the electrolyte and the negative electrode. Thus, a modified electrolyte material is finally obtained.
[0047] The positive electrode is one of lithium iron phosphate LiFePO4, lithium cobalt oxide LiCoO2, lithium manganese oxide LiMnO4, lithium nickel cobalt manganese oxide NCM, and lithium nickel cobalt aluminum oxide NCA.
[0048] like Figure 2 As shown, in the modified electrolyte material, a solid electrolyte interface layer 3 is formed between one side of the electrolyte 2 and the negative electrode 4, and the other side of the electrolyte 2 is connected to the positive electrode after the electrolyte is dripped.
[0049] Embodiment 2:
[0050] On the basis of Example 1, in a practical example of the present invention, the present invention provides a method for preparing a solid electrolyte interface of an electrolyte material, comprising the following steps:
[0051] Step 1: Sinter the prepared Li7La3Zr2O 12 After polishing, it is placed in the reaction chamber of the plasma equipment, and then roughly pumped by a mechanical pump and finely pumped by a molecular pump to remove the air in the reaction chamber, making the internal pressure less than 1×10 -3 Pa; in this embodiment, Li7La3Zr2O 12 For electrolyte.
[0052] Step 2: CF4 is introduced into the chamber at a pressure of 50 sccm. After the pressure is stabilized, the power is turned on, the RF power is set to 400 W, the sputtering time is 5 min, and fluorination treatment is performed to obtain Li7La3Zr2O with a fluorinated layer on one side. 12 ;
[0053] Step 3: Melt the lithium metal sheet at 250°C and coat the Li7La3Zr2O containing the fluoride layer prepared in step 2. 12 One side;
[0054] Step 4: Add LB001 dropwise to Li7La3Zr2O in step 3 12 On the other side, the amount of LB001 added was 3uL / cm 2 ;
[0055] Step 5: Cover the positive electrode of lithium iron phosphate LiFePO4 with the Li7La3Zr2O added with LB001 in step 4. 12 On the other side, encapsulation is performed to complete the formation of an in-situ constructed solid electrolyte interface layer between the electrolyte and the negative electrode, and finally a modified electrolyte material is obtained.
[0056] Embodiment 3:
[0057] On the basis of Example 1, in another practical example of the present invention, the present invention provides a method for preparing a solid electrolyte interface of an electrolyte material, comprising the following steps:
[0058] Step 1: Sinter the prepared Li7La3Zr2O 12 After polishing, it is placed in the reaction chamber of the plasma equipment, and then roughly pumped by a mechanical pump and finely pumped by a molecular pump to remove the air in the reaction chamber, making the internal pressure less than 1×10 -3 Pa; in this embodiment, Li7La3Zr2O 12For electrolyte.
[0059] Step 2: NF3 is introduced into the chamber at 70 sccm. After the pressure is stabilized, the power is turned on, the RF power is set to 400 W, the sputtering time is 10 min, and fluorination treatment is performed to obtain Li7La3Zr2O with a fluorinated layer on one side. 12 ;
[0060] Step 3: Melt the lithium metal sheet at 200°C and coat the Li7La3Zr2O containing the fluoride layer prepared in step 2. 12 One side;
[0061] Step 4: Add LB002 dropwise to Li7La3Zr2O in step 3 12 On the other side, the drip volume is 5uL / cm 2 .
[0062] Step 5: Apply the LiCoO2 positive electrode sheet to the Li7La3Zr2O2 solution in step 4 to which LB002 was added. 12 On the other side, encapsulation is performed to complete the formation of an in-situ constructed solid electrolyte interface layer between the electrolyte and the negative electrode, and finally a modified electrolyte material is obtained.
[0063] Embodiment 4:
[0064] On the basis of Example 1, in another practical example of the present invention, the present invention provides a method for preparing a solid electrolyte interface of an electrolyte material, comprising the following steps:
[0065] Step 1: After sintering, the prepared LATP is polished and placed in the reaction chamber of the plasma equipment. The air in the reaction chamber is removed by rough pumping with a mechanical pump and then fine pumping with a molecular pump to make the internal pressure less than 1×10 -3 Pa; in this embodiment, LATP is the electrolyte.
[0066] Step 2, F2 is introduced into the chamber at 60 sccm, and after the pressure is stabilized, the power is turned on, the RF power is set to 500 W, the sputtering time is 15 min, and fluorination treatment is performed to obtain LATP with a fluorinated layer on one surface;
[0067] Step 3, melting the lithium indium alloy at 300° C. and coating the alloy on one side of the LATP containing the fluoride layer prepared in step 2;
[0068] Step 4: Add LB372 to the other side of LATP in step 3, with a drop volume of 2uL / cm 2 ;
[0069] Step 5: Cover the other side of the LATP to which LB372 was added in step 4 with the NCM positive electrode sheet of nickel cobalt manganese oxide, and encapsulate it to form an in-situ constructed solid electrolyte interface layer between the electrolyte and the negative electrode. Finally, the modified electrolyte material is obtained.
[0070] Embodiment 5:
[0071] On the basis of Example 1, in another practical example of the present invention, the present invention provides a method for preparing a solid electrolyte interface of an electrolyte material, comprising the following steps:
[0072] Step 1: Polish and grind the sintered LAGP and place it in the plasma equipment reaction chamber. Roughly pump the reaction chamber with a mechanical pump and then finely pump the reaction chamber with a molecular pump to remove the air, so that the internal pressure is less than 1×10 -3 In this embodiment, LAGP is the electrolyte.
[0073] Step 2, SF6 is introduced into the chamber at 80 sccm, and after the pressure is stabilized, the power is turned on, the RF power is set to 300 W, the sputtering time is set to 20 min, and a fluorination treatment is performed to obtain a LAGP with a fluorinated layer on one surface;
[0074] Step 3, melting the lithium magnesium alloy at 200° C. and coating the alloy on one side of the LAGP containing the fluoride layer prepared in step 2;
[0075] Step 4: Add LB224 to the other side of LAGP in step 3, with a drop volume of 8uL / cm 2 .
[0076] Step 5: Cover the positive electrode sheet of lithium manganate LiMnO4 on the other side of the LAGP to which LB224 was added in step 4, and encapsulate to form an in-situ constructed solid electrolyte interface layer between the electrolyte and the negative electrode. Finally, the modified electrolyte material is obtained.
[0077] Embodiment 6:
[0078] On the basis of Example 1, in another practical example of the present invention, the present invention provides a method for preparing a solid electrolyte interface of an electrolyte material, comprising the following steps:
[0079] Step 1: Polish and grind the sintered Li6P5S5Cl and place it in the plasma equipment reaction chamber. Roughly pump the reaction chamber with a mechanical pump and then finely pump the reaction chamber with a molecular pump to remove the air, so that the internal pressure is less than 1×10 -3 Pa. In this embodiment, Li6P5S5Cl is the electrolyte.
[0080] Step 2: HF is introduced into the cavity at 60 sccm. After the pressure is stabilized, the power is turned on, the RF power is set to 400 W, the sputtering time is set to 10 min, and fluorination treatment is performed to obtain Li6P5S5Cl with a fluorinated layer on one surface.
[0081] Step 3: melt the lithium indium alloy at 200°C and apply it to the Li7La3Zr2O3 containing fluoride layer prepared in step 2. 12 One side.
[0082] Step 4: Add LB002 to the other side of Li6P5S5Cl in step 3, with a drop of 2uL / cm 2 .
[0083] Step 5: Cover the positive electrode sheet of lithium iron phosphate LiFePO4 on the other side of Li6P5S5Cl to which LB002 was added in step 4, and encapsulate to form an in-situ constructed solid electrolyte interface layer between the electrolyte and the negative electrode. Finally, the modified electrolyte material is obtained.
[0084] Embodiment 7:
[0085] Different from the solid electrolyte surface preparation method of the electrolyte material provided in Examples 1-6, this embodiment also provides another solid electrolyte surface preparation method of the electrolyte material for comparative analysis, which ultimately prepares an electrolyte material without interface modification, comprising the following steps:
[0086] Step 1: Sinter the prepared Li7La3Zr2O 12 Polishing and grinding, among which Li7La3Zr2O 12 It is an electrolyte;
[0087] Step 2: Melt the lithium metal sheet at 200°C and apply it to the polished Li7La3Zr2O 12 One side;
[0088] Step 3: Add LB002 to Li7La3Zr2O in step 2 12 On the other side, the drip volume is 5uL / cm 2 .
[0089] Step 4: Cover the LiCoO2 positive electrode sheet with the Li7La3Zr2O2 to which LB002 was added in step 3. 12 On the other side, encapsulation is performed to complete the formation of an in-situ constructed solid electrolyte interface layer between the electrolyte and the negative electrode, and finally an electrolyte material without interface modification is obtained.
[0090] like Figure 3As shown, the interface impedance test is performed on the modified electrolyte material finally obtained in Example 3 and the electrolyte material without interface modification prepared in this example. The horizontal axis in the figure is the real part of the impedance / ohm, and the vertical axis in the figure is the imaginary part of the impedance / ohm. It can be found that the impedance of the modified electrolyte material with a solid electrolyte interface layer in Example 3 is smaller than the impedance of the electrolyte material without interface modification in this example. It can be seen that a new interface layer is introduced at the interface between the electrolyte and the negative electrode through plasma fluorination treatment, which provides effective contact between the electrode and the electrolyte, improves the uniformity of lithium metal on the electrolyte surface, and reduces the interface impedance.
[0091] like Figure 4 and Figure 5 As shown, the modified electrolyte material finally obtained in Example 3 and the electrolyte material without interface modification prepared in this example were subjected to 0.1C charge and discharge cycle tests, wherein the horizontal axis in the figure is the charge and discharge cycle number, the vertical axis on the left is the specific capacity, in units of mAh / g, and the vertical axis on the right is the coulombic efficiency, in units of %. It can be found that the first-cycle discharge capacities of the modified electrolyte material with a solid electrolyte interface layer in Example 3 and the electrolyte material without interface modification in this example are 119.7 mAh / g and 118.5 mAh / g, respectively, and the capacity retention rates after 100 cycles are 99.9% and 56.6%, respectively.
[0092] It can be seen that the method of the present invention introduces a fluoride layer on the surface of the electrolyte by plasma surface fluorination treatment, and in the process of molten negative electrode coating, the metal lithium is used to react with the fluorine element in the fluoride layer to form a lithium fluoride compound to effectively break the surface tension of the liquid metal lithium, so that the electrolyte has good wettability and lithium affinity, which is conducive to the uniform spreading of lithium metal on the electrolyte surface and reduces the interface resistance; at the same time, after the metal lithium reacts with the fluoride layer, lithium fluoride LiF is generated, and a new interface layer is introduced on the original basis. The new interface layer has extremely high mechanical strength and chemical stability, can effectively inhibit the side reaction at the interface, and promote the lithium ion Li + The uniform deposition of lithium ions can be achieved, the formation of lithium dendrites can be inhibited, and the capacity retention rate and cycle stability of the electrolyte system can be improved.
[0093] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a solid electrolyte interface of an electrolyte material, characterized in that: The steps include: S1. Placing the electrolyte in a reaction chamber of a plasma device and introducing a fluorine-containing gas for vacuum fluorination treatment to obtain an electrolyte having a fluorinated layer on one surface; S2. A solid electrolyte interface layer is in situ constructed between the electrolyte and the negative electrode through the reaction between the fluoride layer on the surface of one side of the electrolyte and the negative electrode, wherein the component of the solid electrolyte interface layer is LiF.
2. The method for preparing a solid electrolyte interface of an electrolyte material according to claim 1, characterized in that: The S1 comprises the following steps: S11, obtaining the electrolyte prepared by sintering; S12, polishing the prepared electrolyte after sintering and placing it in the plasma equipment reaction chamber, and extracting the air in the plasma equipment reaction chamber by a mechanical pump and a molecular pump in turn, so that the internal pressure of the plasma equipment reaction chamber is lower than a preset pressure threshold; S13, introducing fluorine-containing gas into the reaction chamber of the plasma equipment at a preset flow rate until the pressure is stable, turning on the power of the plasma equipment, and performing fluorination treatment based on the set RF power and sputtering time to obtain an electrolyte with a fluoride layer on one surface.
3. The method for preparing a solid electrolyte interface of an electrolyte material according to claim 2, characterized in that: The electrolyte is one of a garnet-type electrolyte, a perovskite-type electrolyte, a NASICON-type electrolyte or a sulfide electrolyte.
4. The method for preparing a solid electrolyte interface of an electrolyte material according to claim 2, characterized in that: The fluorine-containing gas includes one or any combination of fluorine gas F2, carbon fluoride CF4, nitrogen trifluoride NF3, sulfur hexafluoride SF6, hydrogen fluoride HF, and trifluoromethane CHF3.
5. The method for preparing a solid electrolyte interface of an electrolyte material according to claim 3, characterized in that: The S2 comprises the following steps: S21, dissolving the negative electrode at 200° C. to 300° C. and coating the negative electrode on the fluoride layer on one surface of the electrolyte; S22, adding the electrolyte dropwise to the other side surface of the electrolyte; S23, covering the positive electrode on the other side of the electrolyte after the electrolyte solution is added, and encapsulating it, so that the fluoride layer on the surface of one side of the electrolyte reacts with the negative electrode, and completing the in-situ construction of a solid electrolyte interface layer between the electrolyte and the negative electrode.
6. The method for preparing a solid electrolyte interface of an electrolyte material according to claim 3, characterized in that: The negative electrode is one of a metal lithium sheet, a lithium aluminum alloy, a lithium indium alloy, a lithium magnesium alloy, and a lithium titanium alloy; the electrolyte is one of LB002, LB372, LB001, and LB224; the positive electrode is one of lithium iron phosphate LiFePO4, lithium cobalt oxide LiCoO2, lithium manganese oxide LiMnO4, lithium nickel cobalt manganese oxide NCM, and lithium nickel cobalt aluminum oxide NCA.
Citation Information
Cited By
Sodium metal negative electrode material for constructing hybrid solid electrolyte interface layer based on gas-liquid mixed plasma one-step method as well as preparation method and application of sodium metal negative electrode material
CN120127111A
Inorganic solid-state electrolyte lithium lanthanum zirconate surface interface non-metallic element doped modified material using plasma technology and preparation method and application of inorganic solid-state electrolyte lithium lanthanum zirconate surface interface non-metallic element doped modified material
CN120432662A